Plastic pollution pathways from marine aquaculture practices and potential solutions for the North-East Atlantic region. (January 2022) - Skirtun, Maggie; Sandra, Matthias; Strietman, Wouter Jan; van den Burg, Sander W.K.; De Raedemaecker, Fien; Devriese, Lisa I.
Abstract: Aquaculture practices at sea are far from impact neutral and remain an important source of marine plastic pollution. With projected rapid continual growth in the sector, if left unmanaged, aquaculture pollution can have detrimental environmental and social implications. Using the DPSIR framework, the paper examines current practices and pathways of plastic pollution from marine aquaculture in the NE-Atlantic, drawing on findings from literature, stakeholder consultations and beach litter assessments. Pathways for aquaculture-related litter identified include rough weather, farmer behavior, inadequate access to recycling facilities, low price of consumable plastics and high cost of recycling. Beach litter analyses conducted as part of the study exposed serious issues of under quantification, resulting from difficulties in source identification and a lack of detailed categorization in official monitoring systems. The paper makes recommendations to improve litter quantification and waste management, including the use of local knowledge and experts to identify sources of marine litter. Highlights: Plastic pollution from aquaculture at sea is often under quantified Official monitoring systems lack details in terms of litter categorization Use of local knowledge and experts can improve litter monitoring and quantification Better waste management and access to recycling facilities is needed for the sector Increasing the cost of cheap consumable plastics can help prevent gear loss